Targeting Microbiota and Liver Diseases: from Basic Prospective to Recent Advance Treatments - Timur, Paizildaev; Hatem , Mortada Saleh; Jasim, Ihsan Khudhair; Albasri, Ridha Jawad Kadhim; Waleed, Khalid; Nurlanovna, Omorova Aizhan (Trends in Immunotherapy, 2025)
The diverse community of microorganisms residing in the human digestive tract, known as the intestinal microbiome, plays a crucial role in the development and progression of various liver diseases. Disruptions in the gut-liver axis have been associated with various liver conditions, including non-alcoholic fatty liver disease, alcoholic liver disease, viral hepatitis, cirrhosis of liver, and hepatocellular carcinoma. Intestinal dysbiosis can worsen liver disease by promoting systemic inflammation, influencing immune responses, and altering metabolic pathways. This review explores the intricate connection between gut microbiome and liver diseases, highlighting fecal microbiome transplantation as a potential therapeutic approach. Considering search through databases using keywords including “liver disease” AND “microbiome” we found 62 clinical trials out of total 3,303 articles on microbiome changes to find promising treatment of liver disease. Totally 55 articles were assessed, of which most of the studies were about using probiotics, the diet and exercise, and finally FMT. NAFLD was the most predominant liver disease targeted for intervention and treatment. Most of studies (47/55: 85.45%) reported targeting microbiome as an effective and promising treatment. Probiotics and prebiotics also show promise in mitigating liver dysfunction by modulating gut microbiome and influencing adipokines, key regulators in metabolic and inflammatory processes. Despite advancements, significant gaps persist, particularly regarding FMT applications in chronic viral hepatitis and HCC. Further clinical trials are essential to optimize gut microbiome-targeted therapies for liver disease management. This review emphasizes the need for a multidisciplinary approach to bridge the gap between microbial science and therapeutic innovations in hepatology.